2017
DOI: 10.1080/13697137.2017.1315091
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary syndrome of menopause in five Asian countries: results from the Pan-Asian REVIVE survey

Abstract: GSM is underdiagnosed and undertreated in Asia. As discussion of GSM with HCPs appears to be a factor influencing women's awareness and treatment status, a more active role by HCPs to facilitate early discussions on GSM and its treatment options is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“…En relación con la sequedad vaginal como el síntoma más frecuente, nuestros resultados sobrepasan lo reportado en otros estudios, como el realizado por Chua et al en Asia que informan una frecuencia de 57 % (19), y otros que muestran una frecuencia de 27 a 55 %, realizados en poblaciones similares (20)(21)(22)(23).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En relación con la sequedad vaginal como el síntoma más frecuente, nuestros resultados sobrepasan lo reportado en otros estudios, como el realizado por Chua et al en Asia que informan una frecuencia de 57 % (19), y otros que muestran una frecuencia de 27 a 55 %, realizados en poblaciones similares (20)(21)(22)(23).…”
Section: Discussionunclassified
“…Al igual que en otras investigaciones, la sexualidad femenina se ve afectada de forma negativa por la menopausia (8,19); así, se observa que el SGUM se relaciona con serias repercusiones en el deseo, el orgasmo e incremento del dolor, tal como lo confirmamos en este estudio.…”
Section: Discussionunclassified
“…The Revive (Real women's views of treatment options for menopausal vaginal changes) survey of 3046 postmenopausal women with GSM showed VVA has negative impact on the ability to be intimate 62%, to enjoy sexual intercourse enjoyment 65%, to be intimate 61%, women's relationship with partner 55% and sexual spontaneity 54% [33].…”
Section: Negative Impact On Relationshipmentioning
confidence: 99%
“…Laser therapy replenishes glycogen in the vaginal mucosa and allows restoring pH balance of mucosa and therefore improves the symptoms of atrophy and improves sexuality [29]. The Salvatore study showed 85% women regained sexuality within 12 weeks of laser therapy [33]. Long-term data showed that improvement of vaginal health may continue up to 24 months after fractional CO 2 and 80% women decided to start a new treatment cycle of laser applications.…”
Section: Laser Therapymentioning
confidence: 99%
“…Among women who have ever been treated 52% abandoned therapy because they felt improved or cured. The users of GSM treatment reported a high degree of concern mostly related to hormonal therapy and its safety in long-term use (58%) [4]. The VIVA-LATAM study revealed the lack of knowledge of postmenopausal vaginal atrophy in women of Latin America.…”
Section: Introductionmentioning
confidence: 99%